Electrical stimulation in combating pressure ulcer for immobilize subjects: a conceptual framework - Azman, Amelia Wong; Fajingbesi, Fawwaz Eniola; Ahmad, Zuraida; Mohd Mustafah, Yasir; Olanrewaju, Rashidah Funke; Hamzaid, Nur Azah (IOP Publishing, 2019)
. A paradigm shift in health system did intensify the need for research on wearable electronics. There are numerous reasons that could lead to skin ulcers. The most common are lesion due to constant pressure, incontinence control, excessive humidity and postural changes. Over the years, there have been numerous interventions ranging from specific skin treatment, introducing prevention programs as well as to mechanical intervention. On the rise in such clinical rehabilitation program is the use of electrical stimulation (ES) at a therapeutic level, wound care and muscle function restoration. This paper presents a concept development and implementation process of a new pressure ulcer intervention system which can be used for both chairbound and bedridden patients. The concept here is to integrate the use of electrical stimulation, interface pressure mapping and redistribution with antimicrobial protection not only to act as therapeutic but at the same time as a means of prevention of pressure ulcers by improving muscle tone and decreasing atrophy among immobilized subjects.